Men change, and museums change (Cadernos de Sociomuseologia, 2010)
“The object is the continuation of the subject by other means” (Boaventura Souza Santos) This text was written for the 3rd Meeting of the Seminar on Social Museology, which took place at the Museu do Homem do Nordeste [Museum of the North-eastern Man], in Recife, Pernambuco, Brazil, in May 2010. It is important to explain that the Seminar on Social Museology is a monthly cycle of theoretical debates organized with the aim of gathering the necessary contributions to put together a new museological model which can indeed be compatible with the practice and its end activity – to institutionally represent the culture of the north-eastern region – and also with the practice of the role of social agent henceforth given Museums by New Museology in Brazil. To these objectives one can add that of legitimizing the museum before its peers and the museological community understood here as partners of its end activity, which is that of representing the North-eastern Man, a task that can only be feasible if socialized.